The impact of COVID-19 on the mental health of pregnant women in Shanghai, China - Jiali Zhang; Hualong Yuan; Liping Xu; Chuntao Yi; Weiming Tang; Weiming Tang (Frontiers Media S.A., 2022)
BackgroundCOVID-19 has dramatically impacted people's health, especially mental health. This study aimed to compare the psychological status of pregnant women before and after the COVID-19 outbreak.MethodsParticipants were recruited (from September 29, 2019, to November 5, 2020) and screened by the Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder Scale (GAD-7). The study participants were categorized into three groups based on two turning-points: January 23, 2020, when China initiated a locked-down strategy, and May 11, 2020, when Shanghai started to ease the COVID-19 measures. Multivariable logistic regression was used to determine the factors associated with depression and anxiety in pregnant women. We used enter method for variable selection; only variables with P <0.10 were included in the final model.ResultsWe recruited 478 pregnant women. After the outbreak, the depression rate (PHQ-9 ≥ 5) increased by 12.3% (from 35.4 to 47.7%), and the anxiety rate (GAD-7 ≥ 5) was stable (13.3 vs. 16.2%). The multivariable logistic regression results further confirmed that the odds of depression in pregnant women increased 81% after the outbreak (aOR = 1.81, 95%CI: 1.16-2.84). However, the median depression scale score was still statistically higher after the pandemic situation was stable (5.0 vs. 4.0) compared to the outbreak period.ConclusionThe depression rate increased among pregnant women after the outbreak and was not recovered after the ease of COVID-19 measures in Shanghai. Health institutes should pay attention to the long-term influence of the pandemic.